Knowledge Difference Between Before and After Gonorrhea Counseling through Audiovisual Media on the Faculty of Medicine Students, Tarumanagara University Batch 2021 - Luthfiani Sarah Sophia; Irene Dorthy Santoso (Science Midwifery, 2022)
Gonorrhea is a sexually transmitted infection caused by gram-negative cocci bacteria, namely Neisseria gonorrhea. It is the second common cause of bacterial sexually transmitted infections in the world. This infection can affect both men and women, especially in adolescents and young adults. However, the clinical symptoms caused by gonorrhea in men and women are different. In women, gonorrhea often occurs without symptoms. A good level of knowledge can help to reduce the risk of gonorrhea case, one way to help increase knowledge is to conduct counseling. The purpose of this study is to evaluate whether counseling using audiovisual media can improve knowledge about gonorrhea in the students of the Faculty of Medicine, University of Tarumanagara. This study is quasi experimental one group pre-test and post-test design with quantitative data measurement methods. Sampling was done by the simple random sampling technique in collecting samples. The study was conducted in December 2021 - May 2022 on 103 respondents. Data collection used questionnaires and analyzed using Wilcoxon test. The results revealed that 1 respondent (1%) had a good knowledge level, 37 respondents (35,9%) had a sufficient knowledge level, and 65 respondents (63,1%) had a low knowledge level before counseling. Meanwhile, after counseling as many as 95 respondents (92,2%) had a good knowledge level, 8 respondents (7,8%) had a sufficient knowledge level, and no one respondent (0%) had a low knowledge level. In this study, there is a significant difference between the knowledge of gonorrhea before and after counseling using audiovisual media (p <0,0001).